Effects of nanometer alumina and humic acid on the retention and transport of hexavalent chromium in porous media - Ming Wu (Elsevier, 2021)
Column experiments were conducted to investigate the effects of ion type, ion strength, humic acid (HA), and nanometer alumina (NA) particles on the transport of hexavalent chromium (HC) in saturated porous media. A one-dimensional model is developed to simulate the migration of HC affected by NA particles. The results show that nano-alumina particles would enhance the mobility of HC in saturated porous media. However, the influence of NA on the migration of HC in porous media is complex. When the concentration of NA reaches 30 mg/L, HC has minimum retention parameter and best mobility. The transport of HC also is affected by ion strength and ion type. Higher ionic strength would decrease the retention of HC and enhance its mobility. Compared with sodium ion, calcium ion has larger effects on the transport of HC. Moreover, HA can improve the mobility of HC in saturated porous media, but the corresponding promoting effect decreases with the increase of HA concentration. As nanometer contaminants and HC come into the subsurface environment, findings from this study elucidate the key factors and processes controlling the transport of HC in porous media, which can promote the prediction and assessment of HC in the groundwater system.